توظيف نصوص الأفلام الوثائقية في تنمية مهارات التعبير الكتابي للطلبة المتخصصين في اللغة العربية - Tengku Ainul Farha Tengku Abdul Rahman (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The thesis is related to the use of documentary film texts in enhancing Arabic writing skills particularly for Arabic majors at the Arabic Language and Literature Department, International Islamic University Malaysia. The usage started with an analysis of three theories related to the input hypothesis in second language acquisition by Krashen (1981), the cognitive process theory of writing by Flower and Hayes (1981) and the theory of multimedia learning by Mayer et al. (2001). The ADDIE model (analysis, design, development, implement, evaluation) has been chosen as the instructional design in the research framework of this study by using the design and development research by Richey et al. (2004), complemented by the formative evaluation by Tessmer (1993). The participants, who are conveniently sampled for this study, comprised of 12 Arabic subject matter experts, 41 students in the control group (printed text only) and 45 students in the experimental group (both printed and audio-visual texts). The mixed-method approach was employed in this quasi-experimental study by using descriptive quantitative survey, open-ended questionnaire, pre-post tests and participant observation. From the results, the writing skills that can be developed by documentary film texts are skills in choosing a topic, using correct ideas and information, writing conclusions, choosing ideas, sequencing ideas, and developing ideas. As shown by the SPSS mean, there was an increase for the control and experimental groups between the pre- and post-tests, and the increase in the experimental group scores is more than the control group's scores in the post-test. This result shows that audio-visual texts have an effective impact in improving writing skill, in addition to the documentary film written texts presented to students. After the experiment, the students were more interested in learning documentary film texts, felt more motivated and liked to use documentary film texts to develop language skills. This study also investigates the students' opinions about their positive attitudes towards documentary film texts in the development of writing skills and hopefully, this study has contributed to the field of teaching Arabic language skills to non-native speakers.